Association of coffee and tea consumption with the risk of lung cancer: a prospective cohort study from the UK Biobank - Zheng, Shaozhong; Suo, Xiangying; Li, Chunlei; Lu, Shuo; Han, Jintao; Bo, Yacong; Guo, Jing (Frontiers in Nutrition, 2026)
BackgroundThe evidence of relationships between tea and coffee consumption with lung cancer risk remains inconsistent, with few prospective studies exploring dose-response relationships.ResultsThis prospective cohort study included 276,209 participants recruited from the UK Biobank (131,567 male and 144,642 female, mean age of 55.38 ± 8.01 years). Baseline coffee and tea intake was assessed via a touchscreen questionnaire. Hazard ratios (HRs) with 95% confidence intervals (CIs) were derived using Cox proportional hazards regression. Dose-response relationships were assessed via restricted cubic splines. During a median follow-up of 13.26 years, 3,821 participants developed lung cancer. The consumption of coffee and tea demonstrated non-linear associations with lung cancer risk (P for nonlinear < 0.001). Individuals consuming 0.5–1 cup (adjusted HR: 0.72, 95% CI: 0.64–0.81), or 2–3 cups (adjusted HR: 0.77, 95% CI: 0.69–0.86) of coffee daily had a lower risk of lung cancer relative to non-drinkers. Compared with non-tea drinkers, those who drank 0.5–1 cup (adjusted HR: 0.80, 95% CI: 0.70–0.93), 2–3 cups (adjusted HR: 0.67, 95% CI: 0.60–0.76) or ≥4 cups (adjusted HR: 0.86, 95% CI: 0.77–0.95) per day had a lower risk of lung cancer.ConclusionsThis study demonstrated that moderate consumption of coffee and tea was associated with a lower risk of lung cancer. Further studies are needed to confirm these findings and elucidate underlying mechanisms.